"To Be stuck in It—I Can't Just Leave": A Qualitative Study of Relatives' Experiences of Dementia Suffers Living at Home and Need for Support. (October 2013) - Landmark, Bjørg T.; Aasgaard, Heid Svenkerud; Fagerström, Lisbeth
The large number of individuals affected by dementia entails major challenges for home health care (HHC) and dementia-affected families. The aim of the study was to explore and describe relatives' experiences of people with dementia living at home and to reveal the relatives' needs for support. Focus group interviews (10 people) were used for data collection. The analysis was qualitative content analysis. The results show that relatives are unable to escape the situation and that the dignity of the person with dementia is threatened. Relatives experience a sense of powerlessness due to fragmented services. The continuity of HHC services constitutes a major challenge. Personnel should focus more on ethical considerations and on dialogue between formal and informal caregivers.